2000
DOI: 10.1159/000055009
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Trial of a Day-1, -3, -5 Every 3 WeeksPhase I Clinical Trial of Day-1, -3, -5 Every 3 Weeks Schedule with Titanocene Dichloride (MKT 5) in Patients with Advanced Cancer. (Phase I Study Group of the AIO of the German Cancer Society)

Abstract: Background: Titanocene dichloride (TD) is an organometallic compound with antiproliferative properties in vitro and promising antitumor activity in preclinical in vivo models. The drug interferes with DNA, blocks the S/G2 phase of the cell cycle and shows antiangiogenic properties. The purpose of this study was to determine the maximum tolerated dose (MTD) and the dose-limiting toxicity (DLT) of a ‘split’ dose administration schedule (days 1, 3, 5 q 3 weeks). Patients and Method: Patients with prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…The titanocene-and vanadocene dichlorides, (C 5 H 5 ) 2 MCl 2 (M = Ti, V), exhibit antitumor activity for a wide variety of human tumors with reduced toxicity [1][2][3][4]. The biological experiments showed that both the water solubility and the stability of bent [(C 5 H 5 ) 2 …”
Section: Introductionmentioning
confidence: 99%
“…The titanocene-and vanadocene dichlorides, (C 5 H 5 ) 2 MCl 2 (M = Ti, V), exhibit antitumor activity for a wide variety of human tumors with reduced toxicity [1][2][3][4]. The biological experiments showed that both the water solubility and the stability of bent [(C 5 H 5 ) 2 …”
Section: Introductionmentioning
confidence: 99%
“…All studied complexes are effective in the cell division and embodies a strong inhibition of bacterial growth. From the obtained data, it can be estimated that complexes 1 and 2 are more effective than the antitumor agent TDC [22], which has undergone clinical testing before [4,23]. The true inclusion compounds 4, 5, 7 and 8 show similar biological activity as free vanadocene complexes 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…The driving force for the studies on organometallics as reagents to fight cancer has certainly been the promising results already obtained for several organotransition-metal compounds which have been evaluated for their therapeutic properties. Dichloride metallocenes (Cp 2 MCl 2 , M = Ti, V, Nb, Mo, Cp = g 5 -cyclopentadienyl) have shown to exhibit antitumor activity against numerous experimental tumors, e.g., Ehrlich ascites tumor, B 16 melanoma, colon 38 carcinoma and Lewis lung carcinoma, as well as against several human tumors heterotransplanted to athymic mice [2]; titanocene dichloride was already in Phase II clinical trials [3], however it was recently abandoned due to problems of formulation [4,5]. Ferrocene derivatives also showed activity against Rauscher leukemia virus and EAT in CF1 mice [6,7] and in P388 leukemia cells [8] reinoculated tumors [9].…”
Section: Introductionmentioning
confidence: 99%